Preparation method of boron nitride / titanium nitride heterostructure material modified lithium-sulfur battery separator
By using boron nitride/titanium nitride heterostructure materials to modify the separator in lithium-sulfur batteries, the problems of cycle life and energy density of lithium-sulfur batteries under high sulfur load are solved, and the battery performance under high load is achieved promote.
Patent Information
- Application Number
- CN202310171267.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-28
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-02-28
Smart Images

Figure CN116247373B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of energy material preparation and relates to a method for preparing a modified lithium-sulfur battery diaphragm which can alleviate the shuttle effect of a lithium-sulfur battery under high sulfur loading, catalyze sulfur conversion reactions, and improve the cycle stability of the lithium-sulfur battery. Background Art
[0002] With the development of economy and science and technology, the energy structure of mankind is constantly changing towards clean and sustainable directions. At present, lithium-ion batteries with high energy density and long cycle life have become the main power source for consumer electronic products and play an extremely important role. However, with the development of high-energy mobile devices, lithium-ion batteries can no longer meet the current market demand. Compared with traditional lithium-ion batteries, lithium-sulfur batteries are considered to be one of the most promising new energy storage systems due to their ultra-high theoretical specific capacity (1675mAh / g) and theoretical energy density (2600Wh / kg), abundant sulfur reserves and low prices. They can be applied to portable electronic products, power vehicles and large-scale energy storage. However, lithium-sulfur batteries still have many problems and challenges, such as the extremely low electronic and ionic conductivity of the reactant single substance S8 and the final reduction products Li2S2 and Li2S in the battery system, the volume change of the electrode during charging and discharging, and the single substance S8 produces polysulfides soluble in the electrolyte during the battery charging and discharging process, which are easily shuttled to the negative electrode of the battery and deposited on the surface of the metal lithium, causing irreversible loss of active materials in the battery. In addition, the battery electrode material has a volume expansion of up to 80% from the initial state to the final state, which will ultimately lead to low utilization of active materials in lithium-sulfur batteries and poor battery cycle stability, thus restricting the development and application of lithium-sulfur batteries.
[0003] Adding sulfur skeleton materials to lithium-sulfur batteries can effectively improve the conductivity of the electrode, inhibit the shuttle effect of polysulfides, and catalyze sulfur conversion reactions. A lot of work is currently centered around this issue. However, adding skeleton materials to the positive electrode material will proportionally increase the mass of substances on the electrode that cannot provide energy, reducing the battery energy density, which becomes more serious at higher sulfur loadings. A higher sulfur loading is indispensable for the practical application of lithium-sulfur batteries. If special materials are used to modify the battery separator, the battery shuttle effect can be reduced to improve battery performance, while the increase in the electrode sulfur loading will not increase the amount of substances that cannot provide capacity, effectively improving the energy density of the battery at high sulfur loadings. Summary of the invention
[0004] The purpose of the present invention is to address the problem that the "shuttle effect" of polysulfides in the reaction process of lithium-sulfur batteries seriously leads to a sharp reduction in the battery cycle life, and to provide a battery separator modified by an in-situ synthesized boron nitride / titanium nitride heterostructure material, which has a suitable pore size and adsorbs and catalyzes the conversion reaction of polysulfides under the premise of blocking the shuttling of polysulfides. In addition, the amount of modified material on the separator does not increase with the increase of the electrode sulfur loading, and the cycle stability of the battery can be improved at a higher sulfur loading.
[0005] In order to achieve the above object, the technical solution of the present invention includes the following contents:
[0006] A method for preparing a lithium-sulfur battery separator modified by a boron nitride / titanium nitride heterostructure material comprises the following steps:
[0007] S1. Dispersing or dissolving the raw materials in solvent A and stirring evenly to obtain a raw material solution; the raw materials include boric acid and nitrogen-containing organic matter;
[0008] S2, vacuum drying the raw material solution at a first predetermined temperature to obtain a first dried material;
[0009] S3, pyrolyzing the first dried material at a second predetermined temperature for a first predetermined time and then cooling to room temperature to obtain a precursor material.
[0010] S4, adding a predetermined mass of trivalent titanium salt and the above-mentioned precursor material into a predetermined amount of solvent B and stirring evenly to obtain a mixed solution;
[0011] S5, transferring the mixed solution into a round-bottom flask, reflux heating at a third predetermined temperature for a second predetermined time, adding acetone to demulsify after natural cooling, and then filtering; filtering with deionized water and acetone for several times and vacuum drying to obtain a second dried material;
[0012] S6, calcining the second dried material at a fourth predetermined temperature for a third predetermined time under a reducing gas atmosphere to obtain a boron nitride / titanium nitride heterostructure material;
[0013] S7. Coat the obtained boron nitride / titanium oxide heterostructure material on a lithium-ion battery PP separator at a predetermined loading amount, and dry it in a vacuum drying oven at 60° C. to obtain a modified lithium-sulfur battery separator (boron nitride / titanium nitride heterostructure lithium-sulfur battery separator modified material).
[0014] As a preferred aspect, the nitrogen-containing organic matter is one or more of urea, melamine, and dicyandiamide.
[0015] As a preferred aspect, the solvent A includes one of ethanol, acetone and deionized water.
[0016] As a preferred aspect, the solvent B includes one or both of ethylene glycol and glycerol.
[0017] As a preferred aspect, the vacuum drying temperature (first predetermined temperature) is 40-80°C.
[0018] As a preferred aspect, the temperature of the pyrolysis reaction (the second predetermined temperature) is 700-1000°C, and the pyrolysis time (the first predetermined time) is 4-6h.
[0019] As a preferred aspect, the trivalent titanium salt is one or more of titanium trichloride, titanium (III) sulfate, titanium (III) nitrate, and titanium (III) acetylacetonate.
[0020] As a preferred aspect, the reflux heating time (second predetermined time) is 2-4 hours, and the reflux heating temperature (third predetermined temperature) is 160-200°C.
[0021] As a preferred aspect, the reducing gas is one of the following gases: ammonia, a mixture of ammonia and hydrogen, a mixture of ammonia and nitrogen; the fourth predetermined temperature is 700-900°C, and the third predetermined time is 1-3 hours.
[0022] As a preferred aspect, the predetermined loading amount is 0.3-1 mg / cm 2 .
[0023] After adopting the above scheme, the present invention has the following advantages:
[0024] 1. The method of the present invention is simple, easy to operate, simple to post-process, simple in equipment requirements, moderate in cost, and suitable for large-scale production;
[0025] Second, the material has good stability and novel structure, and can effectively inhibit the shuttle effect of polysulfides and has a good catalytic effect on the electrochemical conversion reaction of the battery. It can effectively improve the utilization rate of active sulfur in lithium-sulfur batteries and inhibit the shuttle effect generated during the battery reaction;
[0026] 3. The modified diaphragm synthesized by the method of the present invention enables the battery to have higher battery capacity and cycle stability under high sulfur area loading.
[0027] With reference to the following description and the accompanying drawings, the specific embodiments of the present invention are disclosed in detail, indicating the manner in which the principles of the present invention can be adopted. It should be understood that the embodiments of the present invention are not limited in scope thereby.
[0028] Features described and / or illustrated with respect to one embodiment may be used in the same or similar manner in one or more other embodiments, combined with features in other embodiments, or substituted for features in other embodiments.
[0029] It should be emphasized that the term “include / comprises” when used herein refers to the presence of features, integers, steps or components, but does not exclude the presence or addition of one or more other features, integers, steps or components. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without paying creative labor.
[0031] Figure 1 is a scanning electron microscope image of the boron nitride / titanium nitride heterostructure material prepared in Example 1 of the present invention;
[0032] Figure 2 is an XRD pattern of the boron nitride / titanium nitride heterostructure material prepared in Example 1 of the present invention;
[0033] Figure 3 is a SEM image of the modified diaphragm prepared in Example 1 of the present invention;
[0034] Figure 4 The modified diaphragm prepared in Example 1 of the present invention is used to assemble the battery at 1.5 mg m -2 Sulfur loading and cyclic testing;
[0035] Figure 5 The modified diaphragm prepared in Example 1 of the present invention is used to assemble the battery at 8 mg m -2 Sulfur loading and cyclic testing;
[0036] Figure 6 It is a flow chart of the steps of a method for preparing a lithium-sulfur battery separator modified with a boron nitride / titanium nitride heterostructure material provided in one embodiment of the present invention. DETAILED DESCRIPTION
[0037] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0039] Embodiment 1:
[0040] Take 0.3g of boric acid and dissolve it in 50mL of deionized water, then add 6.9g of urea while stirring, and continue stirring for 12h. After the stirring, the solution is dried under vacuum at 60°C, pyrolyzed at 900°C for 5 hours, and cooled to room temperature to obtain the precursor material. Add 20g of titanium trichloride and 5g of the precursor material to 100mL of ethylene glycol and stir evenly. Transfer the evenly stirred solution into a round-bottom flask, reflux at 195°C for 3h while stirring, add acetone to break the emulsification after natural cooling, and then filter. Filter with water and acetone and vacuum dry. After drying, transfer to an ammonia atmosphere and calcine at 800°C for 2h to obtain a gray-black boron nitride / titanium nitride heterostructure material with a microscopic morphology as shown below. Figure 1 As shown in the scanning electron microscope image of the boron nitride / titanium oxide heterostructure material prepared in this example, the titanium nitride nanoparticles are evenly distributed on the boron nitride without obvious agglomeration.
[0041] like Figure 2 As shown in (XRD diagram of the boron nitride / titanium oxide heterostructure material prepared in this example), XRD shows that there are obvious characteristic peaks of boron nitride and titanium nitride in the material. The composite material is dissolved in a certain amount of deionized water and ethanol solution, and coated on a PP separator with a loading of 0.2 mg / cm, and dried in a vacuum drying oven at 60°C to obtain a modified lithium-sulfur battery separator.
[0042] exist Figure 3 It is found in the SEM image (SEM image of the modified membrane prepared in this embodiment) that the surface of the modified membrane is dense and has covered the holes on the surface of the PP membrane, which can effectively prevent the shuttling of polysulfides. The cross-sectional image shows that its thickness is about 4 microns.
[0043] Figure 4(The modified diaphragm assembled battery prepared in this example is 1.5 mg m -2 Sulfur loading at 2C and cycle test), Figure 5 (The modified diaphragm assembled battery prepared in this example is 8 mg m -2 The performance of the battery assembled with the modified diaphragm at different sulfur loadings is shown in the figure (and cycle test at sulfur loading of 0.1C). Under normal conditions, the battery capacity remains at 826mAh g after 300 cycles at a high current density of 2C. -1 At a high sulfur loading of 8 mg cm -2 The battery can still release 784mAh g after 50 cycles. -1 The capacity is equivalent to a 6.3mAh cm -2 High area capacity density.
[0044] Embodiment 2:
[0045] Take 0.6g of boric acid and dissolve it in 100mL of ethanol, then add 12g of dicyandiamide under stirring, and then continue stirring for 12h. After the stirred solution is dried under vacuum at 50℃, pyrolyzed at 700℃ for 6 hours, and cooled to room temperature to obtain the precursor material. Add 10g of titanium (III) sulfate, 10g of titanium (III) nitrate, and 6g of precursor material to a mixed solvent of 50mL of ethylene glycol and 50mL of propylene glycol and stir evenly. Transfer the stirred solution to a round-bottom flask, reflux at 200℃ for 2h under stirring, add acetone to demulsify after natural cooling, and then filter. Filter with water and acetone and vacuum dry, and after drying, transfer to a mixed atmosphere of ammonia and hydrogen (volume ratio of 1:1) and calcine at 900℃ for 1h to obtain a boron nitride / titanium nitride heterostructure material. The composite material was dissolved in a certain amount of deionized water and ethanol solution, and coated on a PP separator with a loading of 0.5 mg / cm, and dried in a vacuum drying oven at 60 °C to obtain a modified lithium-sulfur battery separator. The battery assembled using the modified separator had a high sulfur loading of 8 mg cm -2 Under the condition of high current density, it can still reach above 730mA / g after 50 cycles.
[0046] Embodiment 3:
[0047] Take 0.6g of boric acid and dissolve it in 50mL of ethanol and 50mL of acetone, then add 6g of dicyandiamide and 6g of melamine under stirring, and then continue stirring for 12h. After the stirred solution is dried at 80℃ in vacuum, pyrolyzed at 1000℃ for 4 hours, and cooled to room temperature to obtain the precursor material. 10g of titanium (III) chloride, 10g of titanium acetylacetonate, and 6g of precursor material are added to a mixed solvent of 50mL of ethylene glycol and 50mL of propylene glycol and stirred evenly. The stirred solution is transferred to a round-bottom flask, refluxed at 160℃ for 4h under stirring, naturally cooled, and acetone is added to demulsify, and then filtered. After filtration with water and acetone, vacuum dry, transfer to a mixed atmosphere of ammonia and nitrogen (volume ratio 1:1) and calcine at 700℃ for 3h to obtain a boron nitride / titanium nitride heterostructure material. The composite material was dissolved in a certain amount of deionized water and ethanol solution, and coated on a PP separator with a loading of 1 mg / cm, and dried in a vacuum drying oven at 60 °C to obtain a modified lithium-sulfur battery separator. The battery assembled using the modified separator had a high sulfur loading of 8 mg cm -2 Under the condition of high current density, it can still reach above 750mA / g after 50 cycles.
[0048] Any numerical value cited herein includes all values of lower and upper values that increase by one unit from the lower limit to the upper limit, and there is at least a two-unit interval between any lower value and any higher value. For example, if the value of the quantity of a component or a process variable (such as temperature, pressure, time, etc.) is stated to be from 1 to 90, preferably from 20 to 80, and more preferably from 30 to 70, the purpose is to illustrate that values such as 15 to 85, 22 to 68, 43 to 51, 30 to 32 are also explicitly listed in the specification. For values less than 1, one unit is appropriately considered to be 0.0001, 0.001, 0.01, 0.1. These are merely examples that are intended to be clearly expressed, and it can be considered that all possible combinations of numerical values listed between the lowest value and the highest value are clearly stated in the specification in a similar manner.
[0049] Unless otherwise indicated, all ranges include the endpoints and all numbers between the endpoints. "About" or "approximately" used with a range applies to both endpoints of the range. Thus, "about 20 to 30" is intended to cover "about 20 to about 30", including at least the specified endpoints.
[0050] It should be understood that the above description is for illustration and not for limitation. Many embodiments and many applications beyond the examples provided will be apparent to those skilled in the art upon reading the above description. Therefore, the scope of the present teachings should not be determined with reference to the above description, but should be determined with reference to the appended claims and the full scope of equivalents possessed by such claims. For the purpose of comprehensiveness, all articles and references, including disclosures of patent applications and publications, are incorporated herein by reference. The omission of any aspect of the subject matter disclosed herein in the preceding claims is not intended to be a waiver of the subject matter, nor should it be considered that the inventors did not consider the subject matter to be part of the disclosed inventive subject matter.
Claims
1. A method for preparing a lithium-sulfur battery separator modified with a boron nitride / titanium nitride heterostructure material, characterized in that: The steps include: S1. Dispersing or dissolving the raw materials in solvent A and stirring evenly to obtain a raw material solution; the raw materials include boric acid and nitrogen-containing organic matter; S2, vacuum drying the raw material solution at a first predetermined temperature to obtain a first dried material; S3, pyrolyzing the first dried material at a second predetermined temperature for a first predetermined time and then cooling to room temperature to obtain a precursor material; S4, adding a predetermined mass of trivalent titanium salt and the above-mentioned precursor material into a predetermined amount of solvent B and stirring evenly to obtain a mixed solution; S5, transferring the mixed solution into a round-bottom flask, reflux heating at a third predetermined temperature for a second predetermined time, naturally cooling, filtering with deionized water and acetone for several times, and vacuum drying to obtain a second dried material; S6, calcining the second dried material at a fourth predetermined temperature for a third predetermined time under a reducing gas atmosphere to obtain a boron nitride / titanium nitride heterostructure material; S7. Coat the obtained boron nitride / titanium oxide heterostructure material on a lithium-ion battery PP separator at a predetermined loading amount, and dry it in a vacuum drying oven at 60° C. to obtain a boron nitride / titanium nitride heterostructure material modified lithium-sulfur battery separator.
2. The method for preparing a boron nitride / titanium nitride heterostructure material modified lithium-sulfur battery separator according to claim 1, wherein: The nitrogen-containing organic matter is one or more of urea, melamine and dicyandiamide.
3. The method for preparing a boron nitride / titanium nitride heterostructure material modified lithium-sulfur battery separator according to claim 1, wherein: The solvent A includes one of ethanol, acetone and deionized water.
4. The method for preparing a boron nitride / titanium nitride heterostructure material modified lithium-sulfur battery separator according to claim 1, wherein: The solvent B includes one or both of ethylene glycol and glycerol.
5. The method for preparing a lithium-sulfur battery separator modified by a boron nitride / titanium nitride heterostructure material according to claim 1, wherein: The vacuum drying temperature is 40-80°C.
6. The method for preparing a lithium-sulfur battery separator modified by a boron nitride / titanium nitride heterostructure material according to claim 1, wherein: The temperature of the pyrolysis reaction is 700-1000°C, and the pyrolysis time is 4-6 h.
7. The method for preparing a boron nitride / titanium nitride heterostructure material modified lithium-sulfur battery separator according to claim 1, wherein: The trivalent titanium salt is one or more of titanium trichloride, titanium (III) sulfate, titanium (III) nitrate, and titanium (III) acetylacetonate.
8. The method for preparing a boron nitride / titanium nitride heterostructure material modified lithium-sulfur battery separator according to claim 1, wherein: The reflux heating time is 2-4 hours, and the reflux heating temperature is 160-200°C.
9. The method for preparing a lithium-sulfur battery separator modified by a boron nitride / titanium nitride heterostructure material according to claim 1, wherein: The reducing gas is one of the following gases: ammonia, a mixture of ammonia and hydrogen, and a mixture of ammonia and nitrogen; the fourth predetermined temperature is 700-900° C., and the third predetermined time is 1-3 hours.
10. The method for preparing a lithium-sulfur battery separator modified by a boron nitride / titanium nitride heterostructure material according to claim 1, wherein: The predetermined loading amount is 0.3-1 mg / cm 2 .